2006
DOI: 10.1086/503047
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Prostaglandin E2by Malaria Parasite Products and Antipyretics Promotes Overproduction of Tumor Necrosis Factor–α: Association with the Pathogenesis of Childhood Malarial Anemia

Abstract: Cytokines and effector molecules are important immunoregulatory molecules in human malaria. Tumor necrosis factor (TNF)-a limits malaria parasitemia but also promotes pathogenesis at high concentrations, whereas prostaglandin E 2 (PGE 2 ) inhibits TNF-a production and is reduced in childhood malaria, at least in part, through suppression of cyclooxygenase (COX)-2 following the ingestion of Plasmodium falciparum hemozoin (pfHz; malarial pigment) by peripheral blood mononuclear cells (PBMCs). Although molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
3
27
0
Order By: Relevance
“…Previous investigations from our laboratory illustrate that phagocytosis of malarial pigment (hemozoin, Hz) by cultured human peripheral blood mononuclear cells (PBMC) generates a profile of cytokine production similar to that observed in children with malarial anemia [27][28][29]. Hz is a Plasmodium-derived biomineralized product of heme, a prosthetic group of hemoglobin (Hb) liberated during Hb degradation [30].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous investigations from our laboratory illustrate that phagocytosis of malarial pigment (hemozoin, Hz) by cultured human peripheral blood mononuclear cells (PBMC) generates a profile of cytokine production similar to that observed in children with malarial anemia [27][28][29]. Hz is a Plasmodium-derived biomineralized product of heme, a prosthetic group of hemoglobin (Hb) liberated during Hb degradation [30].…”
Section: Introductionmentioning
confidence: 84%
“…A number of studies from our laboratory [27][28][29]38], as well as others [49][50][51], have shown that Hz is an important parasitic product that causes dysregulation of de novo cytokine production in human PBMC. As such, Hz was examined as a potential parasitic product that could alter the transcriptional expression of IL-23, IL-12, and IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a crystal form of heme molecules produced by Plasmodium sp., and referred to as hemozoin, also acts as a proinflammatory agonist and thus could be associated with the development of severe forms of malaria (16)(17)(18). Hemozoin inhibits PGE 2 production in both mice (19) and humans (20,21), and there is an inverse relationship between PGE 2 and blood mononuclear cell cyclooxygenase-2 with disease severity in children with P. falciparum malaria (22). Until now there is no clear description of the effect of free heme on the PGE 2 production.…”
mentioning
confidence: 99%
“…Likewise, as antiretroviral therapy is increasingly available in sub-Saharan Africa; future studies among such children would be needed. It is noteworthy that the role of hemozoin in malaria pathogenesis, including PCM, has been extensively studied [15][16][17]. A recent multisite study of 26,000 pediatric malaria cases in sub-Saharan Africa concluded that PCM, while predictive of severe disease and mortality, failed to provide additional prognostic value beyond conventional markers of disease severity [18].…”
mentioning
confidence: 99%